An orphan protein of Fusarium graminearum modulates host immunity by mediating proteasomal degradation of TaSnRK1α - Jiang, Cong; Hei, Ruonan; Yang, Yang; Zhang, Shijie; Wang, Qinhu; Wang, Wei; Zhang, Qiang; Yan, Min; Zhu, Gengrui; Huang, Panpan; Liu, Huiquan; Xu, Jin-Rong (Nature communications, 2020)
Fusarium graminearum is a causal agent of Fusarium head blight (FHB) and a deoxynivalenol (DON) producer. In this study, OSP24 is identified as an important virulence factor in systematic characterization of the 50 orphan secreted protein ( OSP ) genes of F. graminearum . Although dispensable for growth and initial penetration, OSP24 is important for infectious growth in wheat rachis tissues. OSP24 is specifically expressed during pathogenesis and its transient expression suppresses BAX- or INF1-induced cell death. Osp24 is translocated into plant cells and two of its 8 cysteine-residues are required for its function. Wheat SNF1-related kinase TaSnRK1α is identified as an Osp24-interacting protein and shows to be important for FHB resistance in TaSnRK1α-overexpressing or silencing transgenic plants. Osp24 accelerates the degradation of TaSnRK1α by facilitating its association with the ubiquitin-26S proteasome. Interestingly, TaSnRK1α also interacts with TaFROG, an orphan wheat protein induced by DON. TaFROG competes against Osp24 for binding with the same region of TaSnRKα and protects it from degradation. Overexpression of TaFROG stabilizes TaSnRK1α and increases FHB resistance. Taken together, Osp24 functions as a cytoplasmic effector by competing against TaFROG for binding with TaSnRK1α, demonstrating the counteracting roles of orphan proteins of both host and fungal pathogens during their interactions. Fusarium graminearum is a major fungal pathogen of cereals. Here the authors show that F. graminearum secretes an effector, Osp24, that induces degradation of the wheat TaSnRK1α kinase to promote disease while an orphan wheat protein, TaFROG1, can compete with Osp24 for binding to TaSnRK1α and protect it from degradation